2020
DOI: 10.1111/cen.14217
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of circulating microRNAs in thyroid carcinoma: A systematic review and meta‐analysis

Abstract: Background and objective Thyroid cancer (TC) is the most common endocrine system tumour. Several studies had revealed the potential of circulating microRNAs (miRNAs) as novel biomarkers for the diagnosis of TC. The purpose of this meta‐analysis is to summarize published studies and evaluate the diagnostic accuracy of circulating miRNAs in TC detection. Methods In this meta‐analysis, we systematically searched three databases: PubMed, EMBASE and Cochrane Library. We used the bivariate mixed‐effects regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…AUC was 0.939 and the cutoff value was 2.205 (93.8% sensitivity and 88.7% speci city) for combined diagnosis of miR-17-5p and miR-424-5p. Previous studies also elicit that the combination of several different miRNAs, with improved sensitivity and speci city, has elevated diagnostic accuracy relative to individual miRNA [15,29]. Altogether, miR-17-5p and miR-424-5p both could be considered as biomarkers for EMT, and their combination had ampli ed this diagnostic e cacy.…”
Section: Discussionmentioning
confidence: 92%
“…AUC was 0.939 and the cutoff value was 2.205 (93.8% sensitivity and 88.7% speci city) for combined diagnosis of miR-17-5p and miR-424-5p. Previous studies also elicit that the combination of several different miRNAs, with improved sensitivity and speci city, has elevated diagnostic accuracy relative to individual miRNA [15,29]. Altogether, miR-17-5p and miR-424-5p both could be considered as biomarkers for EMT, and their combination had ampli ed this diagnostic e cacy.…”
Section: Discussionmentioning
confidence: 92%
“…Several meta-analyses have been recently published, which studied miRNAs as molecular biomarkers in the diagnosis of thyroid cancer. Of interest, Xu et al [5] found that the summary sensitivity, specificity, and AUROC of circulating miRNAs were 81%, 81%, and 0.88 for distinguishing thyroid cancers from benign thyroid nodules, respectively; and 81%, 85%, and 0.89 for distinguishing thyroid cancers from healthy controls, www.bjbms.org respectively. The results of that study were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous non-coding RNA molecules that regulate transcription and translation, which have gained tremendous attention in research in the last two decades given their ability to regulate gene expression [5,10]. Through the induction of translational repression or silencing effects by complementary binding to target messenger RNAs (mRNAs), these molecules play an important role in the regulation of gene expression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also stated that MiRNAs can help in the diagnosis of malignancy and may be helpful in avoiding unnecessary surgery. It was stated that cir-culating miRNAs should be added in current thyroid nodule evaluations (23) .…”
Section: Discussionmentioning
confidence: 99%